Chloris gayana Kunth under different defoliation regimes. Morphogenesis, sward structure and leaf area index - Ruolo, Maria Soledad; Perez, Hector Eduardo; Rodríguez, Adriana Mabel (2021)
Subtropical pastures are an important alternative to increase forage yields to fulfil cattle nutritional requirements. Despite the increasing expansion of these pastures in the semiarid subtropical region of Argentina, there is very little information about their responses to grazing management. The aim of this study was to evaluate the ef‐fect of different defoliation regimes on morphogenesis, sward structure and leaf area index of one of the most expanded forage species in this region, Chloris gayana Kunth. A combination of two defoliation frequencies (300 and 500 GDD) and two defolia‐tion intensities (1 and 3 green stubble leaves) was compared by a controlled experi‐ment that comprised 1,500 GDD. Defoliation frequency significantly affected leaf elongation rate (LER) and leaf area index (LAI). Under the high defoliation frequency, LER and LAI resulted almost half than under low defoliation frequency (0.34 ± 0.08 vs. 0.67 ± 0.08 mm·tiller−1·GDD−1; 8.31 ± 2.27 m2/m2 vs. 13.27 ± 1.59 m2/m2, at 300 or 500 GDD respectively), regardless of the intensity. Defoliation frequency or inten‐sity did not affect leaf appearance rate, leaf lifespan, leaf size, number of green leaves per tiller nor tiller density at the end of the experiment. We conclude that to maintain high LER and LAI in Chloris gayana Kunth cv. Épica INTA‐Pemán pastures, defoliation frequency could be of 500 GDD. Since leaf lifespan was 415 ± 110 GDD, under this defoliation frequency, a maximum accumulation of green leaf tissues with very little dead tissues may be achieved.